An evaluation of TLS-based glacier change assessment in the central Tibetan plateau - Yuang Xue; Xiaofeng Hong; Xiaobo He; Shichang Kang; Shaoyong Wang; Yongjian Ding (International Journal of Digital Earth, 2024)
Fragmented surfaces and harsh environments have always been the main obstacles hindering observation works of glaciers in central Tibetan Plateau (TP). The advent of Terrestrial Laser Scanner (TLS) technology offers a potential revolution in this context. While TLS has been effectively applied to smaller glaciers in the Alps and Tianshan, this study extends its use to the large and topographically complex Ganglongjiama (GLJM) glacier in the Tanggula Mountains. Over a 5-year period, TLS, with a precision of up to 0.012 m, has documented an accelerated melting trend, with the terminus retreating by 13.305 m and a total mass loss of 2.580 m water equivalent. The research also underscores the role of supraglacial channels and lakes in intensifying surface melting and glacier front instability. Despite challenges in data acquisition due to occlusions and logistical constraints at high altitudes, this first TLS survey of a TP glacier provides invaluable insights into glacier dynamics. Future research could integrate TLS with Unmanned Aerial Vehicle-Structure-from-Motion (UAV-SfM) data fusion to achieve more comprehensive coverage and improve the temporal resolution of observations for a detailed analysis of glacier features.